Septicaemic Melioidosis Complicated by Septic Arthritis in A Bangladeshi male: A Case Report - Haque, Hasna Fahmima; Debnath, Suchismita; Afroze, Samira Rahat; Afroz, Farhana; Rahim, Muhammad Abdur; Musa, AKM (Bangladesh Journal of Medicine, 2018)
Melioidosis is an uncommon disease in Bangladesh but in recent years increasing numbers of cases are being diagnosed. A case of septicaemic melioidosis occurring in a young Bangladeshi returning worker is reported here. The patient presented with fever and features of septic arthritis. Diagnostic work-up revealed the growth of Burkholderia pseudomallei from blood and synovial fluid cultures. This case highlights the importance of high index of clinical suspicion for melioidosis in appropriate clinical scenario. Bangladesh J Medicine Jul 2018; 29(2) : 94-96